Finding Ways to Attract Clients: A Content Analysis of Japanese Language Tutors’ Ads in an Online Tutor Marketplace - Aditya Nur Patria (Diponegoro University, 2021)
The growing number of freelance marketplaces allows students to earn extra money as tutors. The hyper-competitive nature in the marketplaces forces students to compete with non-student tutors in order to get clients (Popiel, 2017). Non-student tutors may be better equipped with a lot of experiences. However, all freelance tutors need to post impressive ads to get their clients, particularly in a niche subject such as Japanese language. The present study explores the differences of information put in ads between student tutors and non-student tutors on a tutor marketplace, Superprof. Content analysis (Cohen et al, 2011) was used to identify categories of information in the ads. The results show that there were 11 categories of information including tutors’ name, origin, current employment status, education background, language proficiency certificate, course level, course type, rhetoric, experience in Japan, coverage area, and availability. The data were then analyzed statistically to find the categories of information with a significant difference. It shows that both groups have difference in putting information related to their current employment status (t = 3.88, p < 0.001, d = 1.05) and their education background (t = 2.78, p < 0.005, d = 0.75). The implication of the study is that student tutors tend to value their relationship with academic institutions and make it as a bargaining power to market their skills in the marketplace.